PEMODELAN KNOWLEDGE MANAGEMEN SERVICE KENDARAAN BERBASIS WEB PADA BENGKEL MOTOR SEKOLAH KEJURUAN - Ahmad Roihan; Radifa Rahma Fitriani (UNIVERSITAS RAHARJA, 2018)
ncreasing the number of vehicles in our country into fertile fields to increase revenue for workshop owners. The increase is also a job opportunity for outomotiv vocational students to get jobs. Implementation of knowledge management into a solution to improve the quality of human resources, especially the graduates smk. Knowledge management is an attempt to increase knowledge useful in the organization. Knowledge management is not only an arrangement of knowledge, but rather the management of an organization with a particular focus on knowledge. Implementation of knowledge management with a web-based system, is expected to be a solution of the needs of the flow of knowledge that is not hindered by time and place limits. The methodology used is contingency factor analysis to get the knowledge management system model. The resulting knowledge management system model supports the Socialization, Externalization, Combination, Internalization (SECI) process. Knowledge management system was developed as a means of knowledge sharing at the workshop of Vocational High School Vocational School.